KECENDERUNGAN GAYA PERANCANGAN BUKU ILUSTRASI ANAK TAHUN 2015-2021 - Wulandari, Dwi; Husna, Inayatul; Hasnan, Haikal; Sukma, Muhammad Abi; Alfiana, Serefina (AKSA: Jurnal Desain Komunikasi Visual, 2024)
Illustrated books have continued to develop by bringing all the changes and developments from year to year, so the trend of illustration books will continue to change. In this article, researchers examine the trend of children's illustrated books in Indonesia with their characteristics published from 2015 to 2021. The method used in this research is the Systematic Literature Review (SLR). The SLR method was used to identify, review, evaluate, and interpret all the latest available research on how children's illustrated book styles were developed. Of the 28 development research articles analyzed, it was found that the font characters for most illustration books use fonts that are easy to read, simple, not stiff, and playful, and each font adjusts its use. The majority of designs use bright, contrasting and striking colours. As many as 21% of children's illustration books use pastel colours. The themes used in the children's illustration books are mostly related to education for children. Most characters in illustration books use cartoon images in the form of human figures. In addition, there are also complementary illustrations to adjust the contents of the existing book. Most of the layouts for children's illustration books use the Picture Window Layout with additional layout emphasis on several sections.